Intercepting and Instrumenting COM Applications - Hunt, Galen; Scott, Michael L. (Fifth Conference on Object-Oriented Technologies and Systems (COOTS), 1999)
Binary standard object models, such as Microsoft's Component Object Model (COM) enable the development of not just reusable components but also an incredible variety of useful component services through run-time interception of binary standard interfaces. Interception of binary components can be used for conformance testing, debugging, profiling, transaction management, serialization and locking, cross-standard middleware interoperability, automatic distributed partitioning, security enforcement, clustering, just-in-time activation and transparent component aggregation. We describe the implementation of an interception and instrumentation system tested on over 300 COM binary components, 700 unique COM interfaces, two million lines of code, and on three major commercial-grade applications, including Microsoft PhotoDraw 2000. The described system serves as the foundation for the Coign Automatic Distributed Partitioning System (ADPS), the first ADPS to automatically partition and distribute binary applications. While the techniques described in this paper were developed specifically for COM, they have relevance to other object models with binary standards, such as individual CORBA implementations.